Pola Aktivitas dan Keanekaragaman Belalang (Insecta: Orthoptera) di Taman Naasional Gunung Ciremai, Kuningan, Jawa Barat - Erniwati, Erniwati (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTPattern Activities and Diversity of Grasshopper (Insecta: Orthoptera) in Ciremai MountainNational Park, Kuningan, West Java. The grasshoppers of the Gunung Ciremai National Park,based on collections in 2008 are reported. The grasshoppers were collected by transect methodin three locations: Seda (508 m asl), Palutungan (1076 m dpl) and Cilengkrang (1143 m asl). Atotal, thirty three species of grasshoppers were recognized. The numbers of species/diversityindex Shanon are: 25/2.99, Palutungan 18/2.60, and Cilengkrang 13 species/2.46. The highestactivity of Ciremai grasshoppers was between 11.00-12.00 pm. The Erianthus sp was newrecord from Java, whereas Oxya spp.and Catantops (Acridiidae) spp were only found onSeda. Bibracte sp.(Acridiidae) and Paratrigonidium faseocinctum (Gryllidae) were only foundon Cilengkrang, whereas Oxyrrhepes obtusa (Acridiidae) was only found on Palutungan.Species similarity on location, observation time, activity, and habitat of each grasshopper arediscussed.Kata kunci : Activities, diversity, grasshopper, orthoptera, insecta, Ciremai